The SEZ Plan for Batam, Bintan, and Karimun: Looking Back and Ahead - Choi, Nankyung (2016)
A YEAR has passed since Indonesian President Susilo Bambang Yudhoyono and Singapore Prime Minister Lee Hsien Loong witnessed the signing of a Memorandum of Understanding to set up special economic zones (SEZs) in Batam, Bintan, and Karimun of the Riau Archipelago, Indonesia. The Joint Steering Committee established under the MoU has since held a series of meetings to discuss the plans to achieve shared objectives. These include increasing exports, attracting investment, and creating jobs in each of the three zones. Although the preparations for the implementation of the SEZ plan have moved ahead, the process has not been smooth.